Persuasive and Humanist Da'wa Message on the Gus Mus' @s.kakung Instagram Account during the COVID-19 Pandemic - Asna Istya Marwantika (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
The COVID-19 pandemic in Indonesia requires contributions from Islamic leaders to educate and provide information to the public. As an Islamic leader, Gus Mus actively responds to this condition through his Instagram account @s.kakung. This study determines Gus Mus's contribution to the da'wa message uploaded by @s.kakung, from the preaching theme and the strategy of delivering da'wa's message. This research uses a qualitative descriptive method with qualitative content analysis techniques data collected from the @s.kakung Instagram account from March 16, 2020 - March 29, 2021. The results showed that the da'wa message uploaded by the @s.kakung in faith, Sharia, and moral. The creed announces that we must never forget Allah, obey Allah's commands in pandemic conditions. Da'wa messages on the Sharia theme, such as making inner efforts, are praying, wirid, sholawat, and Hizib autad practice. The moral theme messages support the movement to help people affected by COVID-19 comply with health protocols by wearing masks, keeping their distance, washing hands, and avoiding crowds. Meanwhile, the strategy of delivering Gus Mus' da'wa messages in the @s.kakung Instagram uses more persuasive and humanist